Tomorrow's education today - National Symposium on Educational Computing (EDUCOMP '96) (1996 : Kuala Lumpur); Malaysian Council for Computers-in-Education (MCCE); Universiti Malaya; Malaysia. Kementerian Pendidikan; Malaysia. Kementerian Sains, Teknologi dan Alam Sekitar (Kuala Lumpur: MCCE, 1996)
44